An inclusive comparative review of valuation methods for assessing environmental goods and externalities. (21st August 2006) - Eshet, Tzipi; Ayalon, Ofira; Shechter, Mordechai
Economists have developed various concepts aimed at proposing monetary values for environmental non-marketed goods. This review analyses the different approaches and reveals most of the methods rely on economic welfare theory, based on the values that individuals ascribe, directly or indirectly, to their preferences regarding an environmental good with no observable price in the market. However, in practice, approximate methods, based on expert judgement and assessment, dominate mostly because they are easier to attain.